The financial (in)stability real interest rate, r** - Ozge Akinci; Gianluca Benigno; Marco Del Negro; Albert Queralto (Federal Reserve Bank of New York, 2020)
We introduce the concept of a financial stability real interest rate using a macroeconomic banking model with an occasionally binding financing constraint, as in Gertler and Kiyotaki (2010). The financial stability interest rate, r**, is the threshold interest rate that triggers the constraint being binding. Increasing imbalances in the financial sector, measured by an increase in leverage, are accompanied by a lower threshold that could trigger financial instability events. We also construct a theoretical implied financial conditions index and show how it is related to the gap between the natural and financial stability interest rates.
Keywords: E4; E5; G0; 330; r**; financial crises; financial stability; occasionally binding credit constraint